Jaringan Sosial Industri pada Kain Gringsing di Desa Adat Tenganan Pegringsingan, Kabupaten Karangasem, Bali - Pratiwi, Ni Komang Rahma Tri (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
The purpose of this research is to explain and analyze how social networks are formed in establishing cooperation in Gringsing fabric industry activities together with other economic actors such as Consumers, Producers, and Distributors. The method used in this study is a qualitative approach with a descriptive-explanatory type. The theory used in analyzing this study is the social network theory by Mark Granovetter. The results of this study reveal that there is a basis for principles that make the formation of a social network between economic actors in the Gringsing fabric industry. The social network formed is based on four principles, namely norms, the strength of weak and strong bonds, other roles that bridge actors, and the interpenetration of economic action in non-economic areas. This study reveals that Gringsing fabric craftsmen as well as producers have succeeded in realizing their economic activities based on the attachment of their social activities through four principles of social networks, namely norms, the strength of weak and strong bonds, other roles that bridge actors, and the interpenetration of economic action against non-economic ones. Keywords: Social network, Gringsing fabric, Economic actor